Principles of Cutting Process Modelling and New Algorithm Proposal - Zeman, Pavel; Kovalčík, Jaroslav; Vrabec, Martin (Manufacturing Technology Journal, 2014)
Nowadays the pressure to increase the efficiency of the machining processes is constantly growing. The efficiency of the machining process can be pursued from two basic perspectives - enhancing the cost-effectiveness of the process (decreasing production costs) or increasing production in time. Via these approaches alone, manufacturers of parts as well as suppliers of machine tools and cutting tools try to improve their position in a highly competitive market. One of the approaches to increase efficiency is the correct choice and subsequent optimal exploitation of the potential of cutting tools and machine tools as well as a reduction in the energy intensity of the cutting processes for a given component. That is what led to the idea of creating an analytical-material model for determining the force interaction between the cutting tool and workpiece, energy intensity and machining process efficiency. The result will be an application that helps technologists in practice to choose correctly the appropriate types of cutting tools, operations, machine tools and also quickly determine the main parameters of the cutting process so that there is the possibility of comparing their results with other variants. The first step and goal is to create an overview of the cutting processes and the associated cutting process modelling, compare their advantages and disadvantages, and then propose an approach of our own.
Keywords: machining; modelling; cutting forces; cutting power; specific cutting force